Ophthalmic products with extracellular matrix components. Their effectiveness in the process of corneal repair in neurotrophic, herpetic, recurrent keratitis and erosions - D.Yu. Maychuk; A.A. Tarkhanova; I.A. Pronkin (Офтальмохирургия)
Introduction. One of the topical issues of modern ophthalmology is the widespread prevalence of corneal blindness among the working-age population. The cause of this condition in most cases are infectious and inflammatory diseases of the anterior segment of the eye, the outcome of which is a violation of the architectonics of the extracellular matrix (ECM) of the cornea, clinically manifested by edema of the stroma, its fibrosis. Purpose. Comparative analysis of the effectiveness of existing ophthalmic agents based on biomimetics of ECM to stimulate the processes of reparative regeneration in neurotrophic, herpetic, recurrent keratitis and corneal erosions. Material and methods. Our literature review has shown the great importance of thecomponents in maintaining corneal homeostasis, its transparency, strength, shape stability, as well as differentiation, proliferation, migration and growth of cellular structures of the ECM, and therefore the need to maintain its physiological architectonics in the treatment of infectious and inflammatory pathology. Results. The range of ophthalmic medicines and medical devices based on biomimetics of ECM is quite diverse. The active substances of such ophthalmic agents are the main components of the ECM, namely, glycosaminoglycans (GAG), glycoproteins, collagen, hyaluronic acid, heparin. Conclusion. Among the many biomimetics, we can single out the multicomponent hydrogel composition «Corneal Epithelium gel Protector (CEGP) SPHERO®oko (JSC «BIOMIR Service», Russia), designed to restore the corneal epithelium, which includes both the main components of ECM and other biologically active substances, including peptides, amino acids, uronic acids, monosaccharides, growth factors, etc. The multicomponent composition of SPHERO®oko provides the microenvironment necessary for the cells of the eye tissues, contributing to the processes of their proliferation and differentiation and, as a final result, to the acceleration of reparative regeneration of tissues damaged as a result of injury or infectious-inflammatory process. And also SPHERO®oko demonstrates anti-inflammatory, decongestant, tear-substituting action, contributes to reducing neovascularization.